Pesticide Provisions of the Florida Agricultura Worker Safety Act (FAWSA) - Frederick M. Fishel (EDIS)
The purpose of this guide is to provide a summary of the pesticide provisions of the recently enacted Florida Agricultural Worker Safety Act (FAWSA) and the definitions that are used in its language. This document is PI-41, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published April, 2005.